Dukungan sosial teman sebaya terhadap optimisme pada mahasiswa double degree - Nikita, Maria; Khotimah, Husnul; Juliadilla, Risa (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Abstract: The changing of learning from direct methods to indirect methods without direct interaction in class, is a challenge for double degree students in D3 English Program at Merdeka University of Malang. The problems found are related to the low level of optimism. This study aims to determine the effect of peer social support on optimism in double degree students. The research method used is quantitative. The sampling technique is a proportionate stratified random sampling of 90 students from 148 population of double degree programs. The method of data collection using Likert scale. The scale items for peer social support (51 valid) and optimism (38 valid) with a reliability coefficient of 0.949 peer social support and 0.918 optimism. Data analysis used simple linear regression analysis with SPSS v.26 program. The results of hypothesis testing show a significance value of 0.000 0.05, which means that there is a significant influence between peer social support on optimism with an effective contribution of 33.4%.Keywords: double degree students; optimism; peer social support